J-integral analysis of the elastic strain fields of ferrite deformation twins using electron backscatter diffraction - Koko, A; Elmukashfi, E; Dragnevski, K; Wilkinson, AJ; Marrow, TJ (Elsevier, 2021)
The strain fields of deformation twins in the ferrite matrix of an age-hardened duplex stainless-steel (Zeron 100: 25%Cr, 7%Ni) have been studied in situ under load, and ex situ (unloaded), using high-resolution electron backscatter diffraction (HR-EBSD). The local two-dimensional (2D) elastic strain field acting on the twin tip was parameterised for the first time using the strain energy release rate (J-integral) and then decomposed into the mode I and mode II stress intensity factors (KI and KII). An improved method to select the strain reference was used, based on the relationship between the HR-EBSD cross-correlation peak height and mean angular error. The elastic field described by KI increased with twin thickness. The in-plane shear field, described by KII, relaxed when the load was removed. Some current limitations of the 2D analysis are discussed, which aims to provide an experimental methodology to quantify the fields that describe the local boundary conditions for twin thickening and propagation.